(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
There are several intersections, in various aspects, between art, crafts, design and they contribute to the conceptual evolution of each of the sectors and, at the same time, to the interaction between them. In this study, there is a concern with the concepts related to art, handicrafts and design, their ambiguities, interrelationships, connections, in their respective updates during different times, which involve actions, technical and material terms, based on social and contextualizations. The methodology used opts for a synthesis and adaptation of the authors: Löbach, Munari and Baxter, in addition to Dijon De Moraes. The image, as visual communication, has different values, according to the context where they are inserted, and offer different information. In the same way that they will remain with greater or lesser intensity (condensing or diluting), for a greater or lesser time in people’s repertoire of images. All these integrative possibilities are offered in relation to the already existing elements and the possibilities of "connections" that they will offer. Your permanence warning will be that of pregnancy in memory, that is, the real time of your true existence, not physical time, but, on the contrary, that of your psychophysical pregnancy, which gives consistency to the Gestalt laws, especially with regard to to its basic law of the pregnancy of form. The creator too. with his non-verbal communication in the artistic universe, he will use the same resource as his "archive of representative meanings" that he brings to memory, in accordance with the ethos of a collective body, as defined by Maffesoli.